PERAN GURU PENGGERAK DALAM PENDIDIKAN MERDEKA BELAJAR - Rizki Wulan Ningsih; Nabila Fatmala; Puri Nuralyanti (Jurnal Bionatural, 2024)
This article discusses the role of driving teachers in independent learning in elementary schools. This article is based on a literature review, use of books and journals, and related documents. The purpose of this article is to provide information about how teachers can use available technology to create engaging learning that encourages students to improve their academic performance. Students are able to be independent in accordance with the Pancasila student profile aspects which require students to have noble character, global diversity, work together, be independent, reason critically and be creative. Independent learning creates students who are high in analysis and understanding when understanding the ability to discuss problems faced in life. In addition, in the classroom, the driving teacher functions as a mentor and teacher for other teachers. Keywords : Motivating Teachers, Freedom to Learn, Pancasila Student Profile.